Exploring Media-Covered Accountability of Public Agencies. Issue 4 (April 2022) - Jacobs, Sandra; Boon, Jan; Wonneberger, Anke; Salomonsen, Heidi Houlberg
Although journalism and media coverage are known to induce, inform, and affect public accountability processes, little is known about media-covered accountability. This study therefore explores accountability processes of Danish and Flemish agencies as subjects of the news. Drawing on news construction literature, our quantitative content analysis of newspaper coverage ( N = 13, 540) focuses on the presence of accountability processes in media coverage and the extent to which organizational characteristics (task, political salience, and size) are related to this phenomenon. Horizontal accountability forums have the highest media presence. Opinions from horizontal forums, vertical forums, and citizens appear less frequently for service-providing organizations.